Linking international norms to regions: Mercosur and ASEAN facing the challenge of cultural diversity - Antonios Vlassis (Política & Sociedade)
The Convention on diversity of cultural expressions (CDCE), adopted by UNESCO in 2005, became a main mechanism within the multilayered global governance of cultural industries, establishing new practices regarding the cultural sector. My article encourages an original view on norm diffusion and implementation focusing on two regions: Mercosur (Southern Common Market) and ASEAN (Association of the Southeast Asian Nations).Through the analysis of the CDCE’s transfer from international level to Mercosur and ASEAN regions, my article seeks to explore four key questions: why do actors engage in norm transfer? Who are the key actors involved in the norm transfer process? What is transferred and why? What restricts or facilitates the norm transfer process?